Molecular Insulin Actions Are Sexually Dimorphic in Lipid Metabolism - Ortiz-Huidobro, Rosa Isela; Velasco, Myrian; Larqué, Carlos; Escalona, Rene; Hiriart, Marcia (Frontiers in Endocrinology, 2021)
The increment in energy-dense food and low physical activity has contributed to the current obesity pandemic, which is more prevalent in women than in men. Insulin is an anabolic hormone that regulates the metabolism of lipids, carbohydrates, and proteins in adipose tissue, liver, and skeletal muscle. During obesity, nutrient storage capacity is dysregulated due to a reduced insulin action on its target organs, producing insulin resistance, an early marker of metabolic dysfunction. Insulin resistance in adipose tissue is central in metabolic diseases due to the critical role that this tissue plays in energy homeostasis. We focused on sexual dimorphism on the molecular mechanisms of insulin actions and their relationship with the physiology and pathophysiology of adipose tissue. Until recently, most of the physiological and pharmacological studies were done in males without considering sexual dimorphism, which is relevant. There is ample clinical and epidemiological evidence of its contribution to the establishment and progression of metabolic diseases. Sexual dimorphism is a critical and often overlooked factor that should be considered in design of sex-targeted therapeutic strategies and public health policies to address obesity and diabetes.